Differences in the Gut Microbiota Composition and Metabolites Associated With Feeding Intolerance in VLBW Infants With a Gestational Age of ≤ 30 Weeks: A Pilot Study - Liu, Xiao-Chen; Sun, Qian; Ji, Yan-Chun; Fu, Li-Zhen; Wang, Zheng-Li; He, Yu; Li, Lu-Quan (Frontiers in Cellular and Infection Microbiology, 2022)
Objective To explore the main variations in gut microbiota compositions, short-chain fatty acid (SCFA) concentrations and autoinducer-2 (AI-2) levels in very-low-birth-weight (VLBW) infants with feeding intolerance (FI). Methods Twenty-seven VLBW infants with gestational ages of ≤30 weeks were divided into the FI group (n=14) and feeding tolerance (FT) group (n=13). The gut microbiota composition and SCFA concentrations and AI-2 levels in feces were detected at 2 and 4 weeks after birth. Results There was no difference in alpha diversity between the two groups at 2 and 4 weeks after birth (P>0.05). Although the Chao index decreased (P<0.05), there was no difference in the Shannon index from 2 weeks to 4 weeks in either the FI or FT group (P>0.05). Additionally, there was no difference in beta diversity between the FI and FT groups at 2 weeks (P>0.05), but there was a significant difference in beta diversity between the two groups at 4 weeks (P<0.05) and a large difference from 2 weeks to 4 weeks in both the FI and FT groups (P<0.05). Furthermore, the composition of the microbiota at 4 weeks was significantly different from that at 2 weeks in the FI group (P<0.05). The Veillonella abundance was lower at 4 weeks in the FI group (P<0.05), but there were no differences in the compositions of the other main microbes between the two groups (P>0.05). Proteobacteria and Firmicutes were dominant in both the FI and FT groups. The concentrations of propanoic, valeric and hexanoic acids were lower in the FI group at 2 weeks, and the levels of isobutyric and valeric acids were lower at 4 weeks after birth (P<0.05). The areas under the curves (AUCs) of propanoic, butanoic and valeric acids in predicting FI were 0.878, 0.816 and 0.744, respectively. Compared with that in the FT group, the relative bioluminescence of AI-2 was lower in the FI group at 2 weeks (P<0.05), and the AUC was 0.736. Conclusions The main composition of the microbiota was not obviously different in infants with FI. Some SCFAs and AI-2 have moderate value in predicting FI.